Pengaruh Konservatisme Akuntansi, Umur Perusahaan Dan Kepemilikan Institusional Terhadap Tax Avoidance - Zebua, Bonifasius; Prima Sadewa (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
This study aims to analyze and test conservatisme accounting, company age and ownership institusional on tax avoidance. The type of research used in this study is a type of quantitative research with a causal associative approach, and the source used is secondary data in the form of annual reports on consumer non-cyclicals sector for six periods. The population in this study were companies in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange during 2017-2022 and there were 87 companies. The research sample was selected based on purposive sampling technique by obtaining 30 companies for 6 periods or 180 observation data. To test the hypothesis using the program EViews series 9. Data were analyzed using the method of panel data regression analysis. The results of this study partially show that conservatisme accounting have an effect on tax avoidance, meanwhile company age and ownership institusional had no effect on tax avoidance. Simultaneously show that conservatisme accounting, company age and ownership institusional have an effect on tax avoidance.